Improvement of PAI Learning Outcomes of Class V Students of SD Negeri 016 Tambusai Through Make A Match Co-operative Learning Model - Nurwahidah, Nurwahidah; Nasution, Zainul Mahdi; Suanto, Suanto (Indonesian Journal of Basic Education, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) of fifth grade students of SD Negeri 016 Tambusai on the material of Q.S. Al-Ma'un through the application of the Make A Match type cooperative learning model. The research method used was Classroom Action Research (PTK) with two cycles. The subjects of this study were 30 fifth grade students of SD Negeri 016 Tambusai in 2024. The instruments used include learning outcome tests, observation sheets, and student response questionnaires. The results showed that the application of the Make A Match model can improve student learning outcomes. The average student score increased from 65 in the first cycle to 80 in the second cycle, and the number of students who reached the Minimum Completion Criteria (KKM) also increased from 60% (18 students) to 87% (26 students). In addition, students showed enthusiasm and active involvement in learning. Thus, the Make A Match model can be an effective alternative learning strategy in improving PAI learning outcomes.